Regional Convergence in Income Inequality Since the EU Integration of Bulgaria - Raycheva, Iva (UNWE Yearbook, 2021)
Economic theory emphasizes on the statement that income level is a major determinant of living standards, the risk for poverty, and social exclusion. Over the years, a number of researchers have focused on the assertion for huge differences between Bulgarian regions in terms of income inequality, along with many other economic indicators. This article examines the differences in Bulgarian districts by their income inequality levels. The study investigates the regional convergence in district income inequality applying different convergence assessment methods.
Keywords: Income inequality; Convergence; Regions; Bulgaria